Anatase TiO2 Nanospindle/Activated Carbon (AC) Composite Photocatalysts with Enhanced Activity in Removal of Organic Contaminant. (8th February 2012) - Zhou, Wuyi; Zhang, Peng; Liu, Weian
Abstract : This paper embarks upon the three levels of analysis ranging from nanoscale materials synthesis to combination and functionality. Firstly, we have prepared anatase TiO2 nanospindles with an even length of about 200 nm and a central width of about 25 nm by hydrothermal synthesis method at 100°C for 6 h. Secondly, we have dispersed TiO2 nanospindles on the surface of activated carbon (AC) and fabricated TiO2 /AC composite via a dip-coating method. Thirdly, the TiO2 /AC composite has been studied as the photocatalyst to remove the organic contaminants in the waste water and exhibits excellent degradation rate in comparison with pure anatase TiO2 nanospindles.